(untitled) (International Journal of Engineering and Computer Science, 2016)
There is an interesting field in data mining called image mining for image processing. Image mining is the association of image data and extraction of hidden data. Data mining is the process of extracting information or knowledge from a wide database. Image mining makes use of texture, color factors and size of an image. Image texture is determined by a feature called Gray Level Co-occurrence Matrix (GLCM).In this case image retrieval feature will be sharp. In order to retrieve features of similar types of image shapes and texture, a feature called Weighted Euclidean distance is used.